Common Mental Disorders and Its Socio-Demographic Correlates Among Women Of Reproductive Age In Urban And Rural Area Of Meerut - Agarwal, Vertika; Jain, Seema; Kumar Garg, Sunil; Singh, Ganesh; Mittal, Chhaya (Indian Journal of Community Health, 2020)
Background: Common Mental disorders are distress states manifesting with anxiety, depressive and unexplained somatic symptoms categorized as ‘neurotic, stress-related and somatoform disorders’ in ICD-10. These are 2-3 times more common in women than in men and also more in urban area than rural. Women of reproductive age are at higher risk especially those with social disadvantage, low income and low education. Aims & Objectives: To assess the prevalence of common mental disorders and associated socio-demographic factors among women of reproductive age (15-49 years) residing in urban and rural area of Meerut. Material and Methods: This was a cross-sectional study done in urban and rural area of Meerut from June 2018 to October 2019. 267 women in reproductive age (15-49years) were interviewed in urban as well as rural area using a predesigned pretested questionnaire regarding socio-demographic profile. Self- Reporting Questionnaire-20 was used to determine presence of common mental disorders. Results: Overall prevalence of common mental disorders among women of reproductive age group was 19.8%(106) with 24.2%(65) in urban and 15.4%(41) in rural area. Statistical analysis revealed that various socio-demographic variables like belonging to urban area (24.2%),being widowed/separated (urban-85.7%;rural-75.0%), belonging to broken family(urban-54.5%%; rural-58.3%), being employed(urban-39.6%;rural-33.3%) and lower socio-economic status(urban-54.5%;rural-40.0%) were significantly associated with presence of common mental disorders. In urban women increasing age was also associated with common mental disorders. Conclusion: The study revealed a high prevalence of common mental disorders in both urban and rural area and a significant association with various socio-demographic variables.